1525. Evaluation of Clinical Outcomes With Fosfomycin for E. coli and Non-E. coli Enterobacteriaceae Urinary Tract Infections. (26th November 2018) - Lee, Tiffany; Glaser, Laurel; Alby, Kevin
Abstract: Background: Fosfomycin is a broad-spectrum oral antibiotic increasingly used for the treatment of uncomplicated and complicated urinary tract infections (UTIs). The Clinical and Laboratory Standards Institute (CLSI) does not support fosfomycin susceptibility testing on urinary isolates outside of Enterococcus faecalis and Escherichia coli . This is in light of building evidence and concern for the presence of chromosomal fosA gene in non- E. coli Enterobacteriaceae. Regardless, clinicians have continued to test and use fosfomycin for these pathogens due to multidrug resistance or intolerance to other agents without ample data on clinical implications. Methods: This retrospective study included patients who received fosfomycin for the treatment of a UTI caused by any Enterobacteriaceae for which fosfomycin testing was performed from March 2016 through April 2018. We separated patients who received fosfomycin for the treatment of UTIs caused by E. coli from those caused by other Enterobacteriaceae for comparison. The primary outcome is the rate of clinical success at 48 hours, defined as the absence of UTI symptoms and normalization of vital signs. The secondary outcome is the rate of recurrent UTIs caused by the same pathogen within 30 days of the index infection. Results: There were 28 separate episodes of E . coli UTIs in 24 patients and 25 separate episodes of non- E . coli UTIs in 26 patients included into this study. Patients were mostly balanced between the two groups and were on average about 64 years old, mostly females (61%), and had an average Charlson Comorbidity Index of 5. All E. coli isolates were susceptible to fosfomycin, while only 82.8% non- E. coli isolates were fosfomycin-susceptible. The rates of clinical success were similar between the E. coli and non- E. coli groups (89.3% vs. 88.5%). There was a higher rate of recurrence of the same UTI with E. coli (15.4%) than with non- E. coli (4.8%). Conclusion: Findings from this small study suggest favorable outcomes with use of fosfomycin for non- E. coli Enterobacteriaceae. Despite recommendations against testing and use of fosfomycin in these pathogens, it appears that in vitro resistance does not always correlate with clinical response. Disclosures: All authors: No reported disclosures.